Assessment of Plasma Cell Leukemia Occurring in Post-Covid-19 Associated with a Paraneoplastic Limbic Encephalitis - Rouvio , Ory; Levi , Itai; Benharroch , Daniel (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
Patients with chronic lymphocytic leukemia represent a high-risk population for COVID-19. Moreover, the response to SARS-CoV-2 vaccination is often absent or inadequate. A 73-year-old obese individual was diagnosed with an acute COVID-19 infection. The patient’s condition improved, but six months later a new deterioration ensued. Following the appearance of pancytopenia, plasmacytosis involved the peripheral blood (35%), as well as the bone marrow (31%), disclosing an osteoclastic pattern. An encephalitis which prevailed at that stage was of the limbic type. It displayed anti-GABA B-antibodies. Therefore, the condition being neither an infection, nor a metabolic disorder, nor a vascular lesion, is most consistent with an autoimmune reaction. The clinical features were consistent with a plasma cell myeloma, associated with a paraneoplastic syndrome. Despite some criteria not being met, the POEMS syndrome was the preferred diagnosis. It was kept alive by a fluid accumulation that filled both pleural gutters and the area around an enlarged spleen. This POEMS case had a connection to COVID-19 through both the initial acute episode and a potential subacute COVID-19 pulmonary disorder that was determined by significant radiologic ground glass changes. In this case, in addition to having plasma cell leukaemia, the patient also experienced hypoxemic respiratory insufficiency and died from respiratory failure. As a result, we have described a POEMS syndrome that was caused by plasma cell leukaemia and complicated by pulmonary COVID-19, possibly with long COVID features.